Identification of the flow experience in gamified educational environment - Aleksić Veljko V.; Ristić Olga M. (University of Kragujevac - Faculty of Pedagogy, Užice, 2021)
Determining and understanding the user experience in gamified educational environments is a contemporary challenge, especially when analyzing the flow experience (balance of challenge and skills, conscious actions, clear goals, clear feedback, sense of control, etc.). The reason for this lies in the assessment tools that most often created and implemented to separate the user from the experience of flow and/or cannot be applied en masse.The paper presents the results of a study in which flow experience was modeled based on data logs (e.g. number of mouse actions or average response time) in gamified educational environment on a sample of 31HE students. The results indicate the existence of correlations between data logs and flow experience dimensions.